2018
DOI: 10.1590/0100-6991e-20181967
|View full text |Cite
|
Sign up to set email alerts
|

Análise do perfil lipídico de pacientes submetidos à gastrectomia vertical e à derivação gástrica em Y de Roux.

Abstract: Objective: to compare the improvements in lipid profile in patients undergoing sleeve gastrectomy (SG) and Rouxen-Y gastric bypass (RYGB). Methods: in a mixed cohort study, we evaluated 334 patients undergoing SG and 178 patients undergoing RYGB at the University Hospital of the Federal University of Pernambuco and at the Real Hospital Português de Beneficência, Recife, PE, Brazil. We measured serum levels of total cholesterol, LDL, HDL and triglycerides preoperatively and at three, six, 12 and 24 months follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
1
8
0
3
Order By: Relevance
“…Further, the lipid profile was apparently more beneficial among patients 3 years after undergoing LSG than among adults with obesity with matched age and BMI. Considering that patients in previous studies had lower triglyceride levels and higher HDL-C levels up to 2 years postoperatively [6,7], LSG could have an even longer positive impact on some of the lipid profile parameters, especially HDL-C, up to 3 years after the procedure. This effect might be explained by the improvement of HDL-C efflux capacity [27].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Further, the lipid profile was apparently more beneficial among patients 3 years after undergoing LSG than among adults with obesity with matched age and BMI. Considering that patients in previous studies had lower triglyceride levels and higher HDL-C levels up to 2 years postoperatively [6,7], LSG could have an even longer positive impact on some of the lipid profile parameters, especially HDL-C, up to 3 years after the procedure. This effect might be explained by the improvement of HDL-C efflux capacity [27].…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, the control group participants were not on any medication. However, in the patient groups the medication details are as: B12, eight (8); neurobion, two (2); vitamin D, twenty-one (21); multivitamins, five (5); a combination of calcium and vitamin D, five (5); proton pump inhibitors, seven (7); iron, nine (9); metformin, one (1) and zinc, one (1). None of the patients were taking aspirin or thiamine supplements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that sleeve gastrectomy has influence in the reduction of low density lipoproteins (LDL-c), total cholesterol (TC ), triglycerides (TG), and in the increase in high density lipoprotein (HDL-c) [11][12][13] . These…”
Section: Reduction Of Excess Weight Dietary Restriction Of Sugarsmentioning
confidence: 99%